Mitral Valve Prolapse and Anxiety Disorders: A Systematic Review of Evidence in Both Directions and Meta-Analysis - Andrea Sonaglioni; Giulio Francesco Gramaglia; Gian Luigi Nicolosi; Massimo Baravelli; Michele Lombardo (Journal of Clinical Medicine, 2026)
Background: The association between mitral valve prolapse (MVP) and anxiety disorders has remained controversial for more than four decades because of heterogeneous psychiatric definitions, evolving echocardiographic diagnostic criteria, and conflicting findings across observational studies. We performed a systematic review to examine the available evidence in both directions of the MVP–anxiety relationship, together with a meta-analysis of anxiety-related outcomes among patients with MVP versus controls, and to evaluate the influence of different echocardiographic diagnostic criteria on this association. Methods: PubMed, Scopus, and EMBASE were systematically searched for observational studies evaluating either direction of the association between MVP and anxiety disorders. Studies assessing anxiety-related outcomes in patients with MVP or the prevalence of MVP among individuals with anxiety disorders were included in the systematic review. Quantitative synthesis was restricted to studies providing comparative data on dichotomous anxiety-related outcomes in MVP and control populations, using random-effects models to calculate pooled odds ratios (ORs) with 95% confidence intervals (CIs), whereas evidence concerning MVP prevalence among individuals with anxiety disorders was synthesized descriptively. Results: Seventeen studies published between 1979 and 2026 met the inclusion criteria, including 10 evaluating anxiety-related outcomes in patients with MVP and 7 assessing MVP prevalence among patients with anxiety disorders. Eight studies evaluating anxiety-related outcomes in MVP versus control populations were eligible for quantitative synthesis, whereas studies examining MVP among individuals with anxiety disorders contributed to the descriptive synthesis. Overall, patients with MVP showed a significantly higher prevalence of anxiety-related outcomes than controls (OR 1.78, 95% CI 1.15–2.75; p = 0.010), with no evidence of between-study heterogeneity (I2 = 0%). The association was significant in studies using 2D echocardiographic assessment but not in those using historical M-mode criteria, with no significant between-subgroup difference (p = 0.227). Meta-regression identified no significant influence of publication year, age, or sex on the pooled estimate. Sensitivity analyses showed that the pooled association was not disproportionately influenced by any single study. Conclusions: Patients with MVP exhibit a significantly increased prevalence of anxiety-related outcomes compared with controls, although no causal relationship or effect modification by echocardiographic method can be established. Conversely, evidence on MVP prevalence among individuals with anxiety disorders remains heterogeneous and currently supports only descriptive synthesis. Future prospective studies integrating standardized psychiatric assessment, contemporary echocardiographic criteria, and quantitative thoracic morphometry are warranted to clarify the underlying mechanisms and clinical implications.